Unusual cause of dyspnoea. Issue 6 (2nd September 2017) - Ullmann, Nicola; Ceglie, Giulia; Paglietti, Maria Giovanna; Bottero, Sergio; Cutrera, Renato
Abstract : A 4-year-old boy was admitted to our department with fever, cough and dyspnoea, unresponsive to salbutamol and antibiotic therapy. He had previously contracted bronchiolitis at 20 days of life, followed by intermittent episodes of wheeze that never required hospitalisation and responded to short inhaled corticosteroid cycles. He had an atopic family history. On examination, he had dyspnoea, persistent cough with bronchospasm but normal oxygen saturations. Bloods showed elevated eosinophils (2004 µL), a slightly elevated C-reactive protein (1.5 mg/dL) and total IgE (326 kU/L), and specific IgE was raised for various inhalant allergens (box ). A chest X-ray was performed (figure 1 ). Questions: 1. What does the chest X-ray in figure 1 show? interstitial pneumonia pneumothorax lung atelectasis with mild mediastinal shift diffuse air trapping enlargement of right hilar lymph nodes 2. Given the clinical picture and the chest X-ray, what would your differential diagnosis include from the following? plastic bronchitis (PB) mycoplasma infection tuberculosis foreign body aspiration lung perforation 3. Are any of these conditions not associated with a specific type of cast/PB? Fontan procedure haemophilia lymphatic abnormalities asthma and other allergic disorders sickle cell disease.